Keanekaragaman dan Karakteristik Habitat Tumbuhan Famili Araceae di Wilayah Kecamatan Jekan Raya Kota Palangka Raya - Rio Eka Desi Purwandari Hartanti; Sulmin Gumiri; Siti Sunariyati (Journal of Environment and Management, 2020)
This study aims to determine the type, level of diversity, and habitat characteristics of the Araceae family that grows in the Jekan Raya District of Palangka Raya City. The purposive sampling method was used to study the Araceae spread over four villages, namely Menteng, Palangka, Bukit Tunggal, and Petuk Ketimpun. The data were collected by observ-ing the morphological part of the sample plants and then were analyzed descriptively. Diversity analysis was carried out using the Shannon-Wiener Diversity index. Diversity analysis of the plants was determined based on the Shannon-Wiener Diversity index. The results show that there have been sixteen (16) types of Araceae plants that grow in the Jekan Raya sub-district of Palangka Raya City, namely: Xanthosoma sagittifolium, Caladium polkagreen, Alocasia plum-bea, Caladium redflash, Colocasia esculenta, Aglaonema costatum, Homalomena rubescens, Caladium polkagreen, Alocasia plumbea, Caladium redflash, Colocasia esculenta, Aglaonema costatum, Homalomena rubescens, Caladium polkagreen, Alocasia plumbea, Caladium redflash, Colocasia esculenta, Aglaonema costatum, Homalomena rubescens, Caladium polkagreen, Alocasia plumbea, Caladium redflash, Colocasia esculenta, Aglaonema costatum, Homalomena rubescens Caladium pinkburst, Spathiphyllum floribundum, Caladium rosebud, Aglaonema legacy, Caladium redstar, Caladium redbelly, and Caladium hortulanum. The characteristics of the habitat are divided into two types, namely the texture of the soil is loamy, slightly sandy and blackish and the habitat is the texture of peat and blackish.